The Influence of the EU Council Presidency on Public Opinion - Petr Kaniok (Romanian Journal of European Affairs, 2012)
The Presidency of the EU Council is regarded as an influential and useful instrument for domestic political progress of European integration and the issues it brings along. Many academics as well as politicians assume that the EU Council Presidency, which allows any country to be at the centre of European and world media attention for six months, therefore represents a strong potential for domestic socialization. This article investigates that idea at the level of public, analyzing several EU Council presidencies, and the potential impact of these presidencies on the voters’ attitudes in the Presidency holding countries on key aspects of the EU. The text’s hypothesis refers to the supposition that the EU Presidency in its present form has a positive influence on the support of citizens for European integration and improvement of their information level on the EU.